A predictive score for retinopathy of prematurity by using clinical risk factors and serum insulin-like growth factor-1 levels - BAYAR, ELİF SAMİYE (IJO PRESS, 2017)
AIM: To detect the impact of insulin-like growth factor-1 (IGF-1) and other risk factors for the early prediction of retinopathy of prematurity (ROP) and to establish a scoring system for ROP prediction by using clinical criteria and serum IGF-1 levels. METHODS: The study was conducted with 127 preterm infants. IGF-1 levels in the 1st day of life, 1st, 2nd, 3rd and 4th week of life was analyzed. The score was established after logistic regression analysis, considering the impact of each variable on the occurrences of any stage ROP. A validation cohort containing 107 preterm infants was included in the study and the predictive ability of ROP score was calculated. RESULTS: Birth weights (BW), gestational weeks (GW) and the prevalence of breast milk consumption were lower, respiratory distress syndrome (RDS), bronchopulmonary dysplasia (BPD) and necrotizing enterocolitis (NEC) were more frequent, the duration of mechanical ventilation and oxygen supplementation was longer in patients with ROP (P<0.05). Initial serum IGF-1 levels tended to be lower in newborns who developed ROP. Logistic regression analysis revealed that low BW (<1250 g), presence of intraventricular hemorrhage (IVH) and formula feeding increased the risk of ROP. Afterwards, the scoring system was validated on 107 infants. The negative predictive values of a score less than 4 were 84.3%, 74.7% and 79.8% while positive predictive values were 76.3%, 65.5% and 71.6% respectively. CONCLUSION: In addition to BW <1250 g and IVH, formula consumption was detected as a risk factor for the development of ROP. Breastfeeding is important for prevention of ROP in preterm infants.
Keywords: retinopaty of prematurity; insulin-like growth factor-1; breast milk; protectivity; POSTNATAL WEIGHT; BIRTH-WEIGHT; BINDING-PROTEINS; INFANTS; GAIN; MILK